Rainfall-induced wind erosion in soils stabilized with alkali-activated waste materials - Alireza Komaei; Abbas Soroush; Seyed Mohammad Fattahi; Hesam Ghanbari (Journal of Rock Mechanics and Geotechnical Engineering)
This study evaluates the efficacy of sustainable erosion control using slag-based alkali-activated cement crusts under varying rainfall and wind conditions. The rainfall intensities ranged from 30 mm/h to 120 mm/h, with durations ranging from 15 min to 90 min, and crust slopes of ∼2° (gentle) and 30° (steep). Wind tunnel experiments were conducted at wind velocities of 14 m/s, 21 m/s, and 28 m/s to investigate post-rainfall wind erodibility, along with changes in crust strength and microstructure analysis. The findings show the development of hydrated cementitious phases in alkali-activated material, which form around and between the particles during the alkaline activation process. Alkali-activated cement crusts significantly reduced erosion caused by rainfall and subsequent wind by several orders of magnitude. At the highest rainfall intensity of 120 mm/h, rainfall erosion was measured to be 1654.81 kg/m2 for untreated samples and 0.89 kg/m2 for treated samples, demonstrating a substantial 99.95% reduction in erosion due to the treatment. Similarly, at the highest wind speed tested, wind erosion was 122.75 kg/m2 for untreated samples and 0.095 kg/m2 for treated samples, indicating a significant 99.92% reduction in erosion due to the formation of an alkali-activated cement crust on the soil surface. However, exposure of the samples to 120 mm/h rainfall for 90 min resulted in a 5.2-fold increase in wind erosion compared to pre-rainfall conditions. Similarly, penetrometer results indicated a 37%–54% reduction in post-rainfall surface strength.